Potential induction of the relative mRNA expression levels of CYP450 by Zhicaowu-Hezi (Aconiti kusnezoffii radix preparata and Terminalia chebula Retz.) - Zhu, Junxuan; An, Ming; Wang, Weiting; Guo, Jingjing; Chen, Mengting; Fang, Longlong; Wang, Cen; Zhang, Dong; Wu, Guodong (Frontiers in Pharmacology, 2025)
BackgroundProcessed Aconiti Kusnezoffii Radix (Aconiti kusnezoffii Radix Preparata, Zhicaowu) and Terminalia chebula Retz. (Hezi) are a classic herb pair in Mongolian medicine, where Hezi mitigates Zhicaowu’s hepatotoxicity. Despite extensive studies on their detoxification effects, the role of cytochrome P450 (CYP450) modulation remains unclear.AimThis study aimed to systematically evaluate the regulatory effects of Zhicaowu and Hezi combination on both enzymatic activity and mRNA expression of CYP450 isoforms (CYP1a2, CYP2b1, CYP2c11, CYP2c13, CYP2d2, CYP2e1, and CYP3a1), and to explore their correlation with hepatoprotective effect.MethodsThe effects of Zhicaowu-Hezi formulation on CYP450 enzymes were systematically evaluated through integrated in vivo and in vitro approaches. Rats received 14-day oral administrations of either Zhicaowu, Hezi, or their combinations (1:1, 1:3, 3:1 ratios), followed by comprehensive assessment using: (1) cocktail probe drug assays monitoring seven CYP450 isoforms (CYP1a2, 2b1, 2c11, 2c13, 2d2, 2e1, 3a1) with HPLC quantification methods for substrate detection, (2) RT-qPCR analysis of hepatic CYP450 mRNA expression, and (3) parallel in vitro studies employing rat liver microsomes to verify enzyme activity changes. These pharmacological evaluations were correlated with histopathological and biochemical indices to establish mechanistic relationships between CYP450 modulation and hepatotoxicity attenuation.ResultsPathological and biochemical analyses confirmed Hezi’s hepatoprotective effects against Zhicaowu-induced toxicity, with the 1:3 Zhicaowu-Hezi combination showing optimal efficacy. In vivo pharmacokinetic studies revealed that Zhicaowu significantly inhibited CYP1a2, CYP2d2, CYP3a1, and CYP2c11 activities, as demonstrated by marked increases in the AUC(0-t), AUC(0-∞)), and Cmax values of their respective probe substrates (theophylline, metoprolol, testosterone, and diclofenac), along with significantly prolonged t1/2 z and reduced CLz/F. It is worth noting that the combined use of Hezi effectively reversed these changes by inducing CYP450, causing significant alterations in the pharmacokinetic parameters of these four substrates. Complementary in vitro studies using liver microsomes consistently showed that Hezi treatment significantly enhanced the metabolic clearance of these four substrates. At the molecular level, RT-qPCR analysis demonstrated that Zhicaowu significantly suppressed hepatic CYP1a2, CYP2d2, CYP3a1, and CYP2c11 mRNA expression, while Hezi co-treatment restored their expression to normal or elevated levels.ConclusionHezi dose-dependently induced CYP450 enzyme activity, reversing Zhicaowu’s inhibition of CYP1a2/2d2/3a1/2c11 and markedly improving liver function and histopathology. These results elucidate the scientific basis for toxicity reduction in Zhicaowu-Hezi herb pair through metabolic enzyme regulation, supporting its traditional use. Future studies will focus on toxic alkaloid (e.g., aconitine) pharmacokinetics and their transcriptional regulatory pathways.